O obesogênico tributilestanho induz adipogênese anormal nos ovários de ratas adultas - Araújo, Julia Fernandez Puñal de (2018)
Tributyltin (TBT) is an obesogen associated with various metabolic and reproductive dysfunctions after in utero exposure. However, few studies have evaluated the obesogenic effect of TBT on adult ovaries. In this work, we evaluated the effects of this pollutant on the reproductive tract of adult female rats, as well as the obesogenic effect on these organs. For this, TBT was administered for 30 days in Wistar female rats at 12 weeks of age and with normal estrous cycle. During treatment, this cycle was followed, and we observed changes in phases and length. We also evaluated the biometric parameters and the morphology of the reproductive system, focusing on ovary and uterus. Were made dosages of sex hormones (LH, FSH, progesterone, estrogen and testosterone), noting that their levels were altered. In addition, it was observed that the steroidogenic pathway was altered in treated animals. We also evaluated the expression of proteins and mRNA of factors that regulate adipogenesis. These animals demonstrated abnormal ovarian adipogenesis with increased cholesterol levels, increased lipid accumulation and increased expression of PPARγ, C/EBP-β and Lipin-1. A negative correlation was observed between ovarian PPARγ expression and aromatase expression in TBT rats. In addition, exposure to TBT resulted in atrophy, inflammation, oxidative stress and fibrosis in the reproductive tract. Ovarian dysfunctions also occurred along with uterine irregularities and abnormal adipogenic ovary markers of TBT animals, may be associated with these uterine irregularities, as a positive correlation was observed between ovary cholesterol levels and uterine inflammation in TBT rats. These findings suggest that TBT leads to ovarian obesogenic effects directly by abnormal adipogenesis and/or indirectly through irregularities in the reproductive tract.